Multiple bilateral supernumerary mandibular premolars in a non-syndromic patient with associated orthokeratised odontogenic cyst- A case report and review of literature - Vikrant O Kasat; Harish Saluja; Jitendra V Kalburge; Yogesh Kini; Atul Nikam; Ruchi Laddha (Wolters Kluwer Medknow Publications, 2012)
Multiple supernumerary teeth are very rare, accounting for less than 1% of cases. They are commonly associated with syndromes like Gardner's syndrome and cleidocranial dysostosis and cleft lip and palate. Non-syndromic multiple supernumerary teeth have a predilection to occur in the mandibular premolar region. Orthokeratinized odontogenic cyst (OOC) is a relatively uncommon developmental cyst comprising about 10% of the cases that had been previously implied as odontogenic keratocysts. More than half of the cases of OOC are associated with impacted tooth; but not a single case of OOC associated with supernumerary teeth is reported. Hence, the purpose of this article is to report the first case of multiple supernumerary mandibular premolars associated with OOC in a 35-year-old male and to review the literature associated with multiple bilateral supernumerary mandibular premolars.